Gummosis, Brown Spot and Seedling Mortality in Su-babul I. Disease Incidence and Pathology of the Host - Singh, Sujan; Khan, S. N.; Misra, B. M. (Indian Forester, 1983)
A serious disease causing gummosis and canker on stem, branches, racbii and peduncles; dark brown spots on leaflets, rachii, peduncles, young twigs, pods and seed and morlity in natural regeneration is recorded on various varieties of Leucoena leucocephala and on L. diversifolia incidence and intensity of the disease in different localities and detailed symptoms are given. The causal fungus is identified as Fusarium semitectum. The fungus has been described in culture isolated from diseased Leucaena plants. The disease was successfully reproduced on healthy plants by artificial inoculations of both stem and leaves. Cankers were found to take double the time to deVelop on stem when inoculations were made on intact surface (72 days) than on injured sUrface (36 days). Root-rot in seedlings was also successfully reproduced by sowing seeds inoculated with F. semitectum. Studies on pathological anatomy of diseased parts revealed that in stem and branches, gum cavities were formed in Phloem and Phelloderm tissues Some gummy deposits were also observed in epidormal and pallisie tissue of leaffets, in exocarp cells of affeectcd pods, in intervening spaces of sub-epidermal cells and in parenchyma cells of seed coats and in cortical cells of arfected roals. Fungal hyphae were found to spread both intra and intercellularly in the affected tissues.